Speech exercises for forming specific communicative competences in context of developing dialogical speech in gagauz language - Coceanji, Nadejda (CEP USM, 2024)
In the article, the author describes the importance and features of the speech situation, notes its role in the formation of communicative competence in the Gagauz language. The author emphasizes the feasibility of interactive learning. The article describes in detail the characteristics of micro- and macro-situations, in the context of thematic units. Here the emphasis is on the development of speaking as a productive type of speech activity through which oral verbal communication is performed. The goal of teaching speaking in the Gagauz language and literature lesson is the formation of such speech skills that would allow the student to use them in extracurricular speech practice at the level of communication in a social environment. The topics of speech situations and assimilated dialogues should cover the range of life situations that are typical for the conditions of students’ daily activities at school, at home, in the street, etc.

В статье автор описывает важность и особенности речевой ситуации, отмечает ее роль в формировании коммуникативной компетенции на гагаузском языке. Автор подчеркивает целесообразность интерактивного обучения. В статье подробно обозначены характеристики микро- и макроситуаций, в разрезе тематических единиц. Здесь делается акцент на развитие говорения, как продуктивного вида речевой деятельности, через который выполняется устное вербальное общение. Целью обучения говорению на уроке гагаузского языка и литературы обозначается формирование таких речевых навыков, которые позволили бы учащемуся использовать их во внеучебной речевой практике на уровне общения в социальной среде. Тематика речевых ситуаций и усваиваемых диалогов должна охватывать тот круг жизненных ситуаций, который характерен для условий повседневной деятельности учащихся в школе, дома, на улице и т.п.
Речевые упражнения для формирования специальных коммуникативных компетенций в условиях развития диалогичной речи на гагаузском языке
Keywords: speech situation; Gagauz language; communicative exercises; interactive learning; speaking; topics of speech situations; social environment; communication; речевая ситуация; гагаузский язык; коммуникативные упражнения; интерактивное обучение; говорение; тематика речевых ситуаций; социальная среда; общение